Kepemimpinan Berbasis Gender: Systematic Literature View - Rohim, Ahsan Zainur; Rohmawati, Amalia; Fitriyah, Az-zahrotul; Lillah, Fala Tania; Putra, Riyan Sisiawan; Fatimah, Nuzulul (Jurnal Ekonomi, Pendidikan dan Pengabdian Masyarakat, 2024)
Gender-based leadership has become an increasingly important topic in management and organizational research, given the global push to achieve gender equality and empower women in the workplace. With more women participating in various economic and political spheres in Indonesia, this phenomenon has become even more significant. This study aims to conduct a systematic literature review (SLR) on gendered leadership. By reviewing existing studies, this research will identify patterns, challenges, and opportunities in promoting gender equality in leadership in Indonesia. The research uses a literature review type of research. The main source of data in this literature review is secondary data. Leadership is influenced by complex and dynamic gender factors. Through a comprehensive research methodology, this article discusses various important aspects of gender-based leadership. Gender in leadership highlights how gender roles influence leadership style and effectiveness. Thus, a deeper understanding of gendered leadership can help identify effective strategies to empower leaders from different gender backgrounds.